Paul Erdmann Isert (1755-1789), médecin naturaliste sur la côte de Guinée : une source pour une histoire des paysages - Dominique Juhé-Beaulaton (Afriques)
Isert was a doctor and a scientist of the 18th century. Although he wrote a travel report considered as a major source for the history of the populations on the Guinea coast, his contribution to the natural science remained unrecognized. He is nevertheless a pioneer of the botanical exploration in this region of Africa and he contributed to the knowledge of the West Africa flora by sending herbarium samples, which are kept in several European cities. His report contains numerous descriptions of the landscapes and references to botanical species identified according to the Linnaean classification system and represents a fundamental source to restore the landscapes of this period. In this article we shall recall the life and scientific progress of this naturalist who is representative of his time and then see how the data, which he passed on to us concerning the flora, can be analysed to reconstitute the history of the landscapes in the region in question.